2002
DOI: 10.1536/jhj.43.103
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Cytokine Release in Patients with Unstable Angina after Coronary Angioplasty.

Abstract: The aim of the present study was to investigate inflammatory cytokine release and the interaction with platelets in patients with unstable angina (UA) after coronary angioplasty. In 50 patients with stable angina (SA) and 58 patients with UA, serial venous blood samples were obtained immediately before, and 30 minutes, 4, 12, 24, 48 and 72 hours, and 7 days after coronary angioplasty. Plasma concentrations of IL-8 and vWF were determined by immunoassay, while the expression of CD11 b/CD18 on monocytes and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 41 publications
1
11
0
Order By: Relevance
“…However, as discussed above, we and others have demonstrated the importance of these values for evaluating the contribution of inflammatory changes in patients following PCI. 3,4,14) Conclusions: Our study shows that preprocedure plasma levels and peak levels of IL-8 provide a more powerful predictor of cardiac events and restenosis than other factors considered thus far in patients with PCI. Low preprocedural IL-8 levels may help identify patients with a good outcome who did not require additional treatment after PCI.…”
Section: )mentioning
confidence: 74%
See 4 more Smart Citations
“…However, as discussed above, we and others have demonstrated the importance of these values for evaluating the contribution of inflammatory changes in patients following PCI. 3,4,14) Conclusions: Our study shows that preprocedure plasma levels and peak levels of IL-8 provide a more powerful predictor of cardiac events and restenosis than other factors considered thus far in patients with PCI. Low preprocedural IL-8 levels may help identify patients with a good outcome who did not require additional treatment after PCI.…”
Section: )mentioning
confidence: 74%
“…One of our previous studies 3) revealed that IL-8 concentrations showed a remarkable increase in the unstable angina group pre-and post-PCI. A sizable cardiac release of IL-8, however, occurs after recanalization of the stenosis vessel even in patients with stable angina who had a normal level of IL-8 before PCI.…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations